EDUCAÇÃO LINGUÍSTICA EM LÍNGUA INGLESA, EM CENA: LETRAMENTO TEATRAL CRÍTICO - Lindomar Cavalcante de Lacerda Lima (2024)
This doctoral thesis is linked in the areas of Applied Linguistics, and has the general objective of analyzing the decentralization of the grammatical focus in English language teaching to a different perspective, located in the field of Critical Literacy and Critical and Decolonial Linguistic Education based on a didactic proposal of critical theater literacy with basic education students. Thus, theoretical dialogues were developed between Applied Linguistics (Moita Lopes, 2006, 2009; Fabrício, 2006; Pennycook, 2006; Moita Lopes; Fabrício, 2019; Kleiman, 2013, 2019; Signorini, 1998), Critical Literacies studies (Janks, 2010, 2016; Jordão, 2016; Menezes de Souza, 2011), Critical, expanded and decolonial Linguistic Education, especially in/of the teaching of English, studies on Theater of the Oppressed (Boal, 1991) and on Poor Theater (Grotowski, 1987) which allow for their genesis a debate of ideas between learners/ actors and the teacher/director thus promoting decolonial practice for a critical and expanded linguistic education, together with studies of decolonial thought from the Modernity/Coloniality group (Castro-Gómez, 2005, Quijano, 2005, 2010 Lander, 2005, Mignolo, 2003, 2005, 2008 2017), decoloniality (Walsh, 2009), with linguistic education in English as the research theme in the context of my own practice as a public school teacher in the city of Campo Grande, state of Mato Grosso do Sul. Methodologically, We opted for action research (André, 1995; Thiollent, 2011) due to my participation in decolonizing my pedagogical practice. To generate the data, proposals for themes were used to produce texts, organization into groups, production of pieces in Portuguese, translation into English, requirement that each person in the group copy the text in full, meetings in the courtyard for the group rehearsals, filming and photographs of rehearsals, field diary, initial questionnaire, final questionnaire. The results show that the didactic proposal of critical theatrical literacy contributed to the development of students' reflective critical sense concerning the English Language, together with this, there was more security when it came to learning the four linguistic skills: speaking, reading, writing, listening, in contextualized ways, which is only possible through Language Education. Therefore, reading and textual comprehension activities were previously carried out only with dictionaries or the teacher reading and translating. After using this critical-reflective theatrical proposal, it was evident that learning a language becomes more significant, highlighting the rationality contemplated in the emotion of theatricalized social practice.